Dynamic capabilities and target costing in Swedish publicly traded companies / Jan Alpenberg and D. Paul Scarbrough - Alpenberg, Jan; Scarbrough, D. Paul (Faculty of Accountancy, 2013)
The increased importance of product development can be seen in both recent research on Dynamic Capabilities as well as research on the use of Target Costing (TC). The Dynamic Capabilities literature is primarily developed in the USA and Europe, while the TC practice is rooted in Japanese practices and has been transferred to the west. This study examines the relationship between the Dynamic Capabilities of the product development team and the implementation of Target Costing (TC) in publicly traded companies in Sweden. Using established concepts from both the Dynamic Capabilities and Target Costing literatures we find partial support for the relationship. We suggest that there may be a bias in the development of Dynamic Capability research that does not comprehend organization practices such as those seen in Japan, Sweden and in Lean Production Organisations more generally. Reasons for this are discussed and proposals for further research are proposed.